(untitled) (Italian Journal of Public Health, 2009)
Introduction: Rare diseases present unique challenges to meet the numerous and varied needs of the rare diseases community and it is required to identify and address these needs. Significant financial and personnel resources are required to address these needs identified. The Office of Rare Diseases Research (ORDR) at the USA National Institutes of Health (NIH) has attempted to meet many of these needs in collaborative efforts with the research Institutes and Centers of NIH and other partners in the private and public sectors in the USA and around the world. Several of the activities of the NIH and the ORDR are presented as possible collaborative efforts available to research investigators and include the Rare Diseases Clinical Research Network, the Bench-to-Bedside research program at NIH, the Genetic and Rare Diseases Information center, the genetic test development program, and the information on clinical research studies made available through Clinical trials.gov. The value of an appropriate family medical history is discussed as are the provisions of the Genetic Information Non-Discrimination Act of 2008 (GINA). Definitions of rare or orphan diseases vary from country to country and may cause some confusion to the rare diseases community. Conclusions: Rare diseases are not limited by geographical or historical boundaries and global partnerships of the rare diseases community are experiencing rapid expansion to assist in the development of orphan products for the prevention, diagnosis and treatment of rare diseases and conditions. The unmet needs of the rare diseases community require additional innovative research and educational programs to reach the extensive global populations affected by the thousands of different rare diseases including activities with the National Organization for Rare Disorders and the Genetic Alliance.